Preoperative Risk Facors to Convert from Laparoscopic Cholecystectomy to open Cholecystectomy - Firas Kamel Maseer Al-Azawii,; Naiem, Nabil Isam; Salih, Salam Adil (Pakistan Journal of Medical & Health Sciences, 2022)
Background: preoperative prediction difficult Laparoscopic cholecystectomy can help the patient as well as the surgeon prepare cholecystectomy Aim to evaluate preoperative risk factors for conversion from Laparoscopic to open cholecystectomy in our setting Patients and Methods: This prospective study include 210 patients who underwent Laparoscopic cholecystectomy from January 2014 to January 2016 in 3rd surgical unit, Baghdad Teaching Hospital ,Shahid ahmed ismail hospital , Heet General Hospital Full clinical history, preoperative examination, laboratory investigation U/S results and intraoperative details were analyzed to determine risk factors of difficult Laparoscopic cholecystectomy. Results: Of 210 patients 12(5.7%) required conversion to open cholecystectomy Significant predictors of conversion were 1 Body mass index ≥ 30 kg/m2. 2 Male gender. 3 Past history of acute cholecystits. 4 Past history of upper abdominal surgery. 5 Gall Bladder wall thickness exceeding 3mm. And the causes of conversion are: 1 In ability to delineate anatomy which occurred in (8) 66.7%. 2 Bleeding which occurred in (3) 25% and, 3 Suspected CBD injury which occurred in (1) 8.3%. Conclusion: Clinical and U/S factors can help predict difficult Laparoscopic cholecystectomy and likelihood conversion of ( Laparoscopic cholecystectomy) to (open cholecystectomy).